Florida contingent - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a group of marchers with a banner that reads, "Florida" during the National March on Washington for Lesbian and Gay Rights. The letter 'o' in Florida is represented by a smiling sun graphic.